1990
DOI: 10.1104/pp.94.1.350
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Photosynthate Partitioning into Starch in Soybean Leaves

Abstract: Studies conducted in controlled environments indicate that daylength affects the proportion of photosynthate stored in leaves as starch or sucrose. To examine the response of partitioning to natural daylight, soybeans (Glycine max [L.] Merr. cv Williams)were grown at 12 different times between May and November in a constant temperature greenhouse without supplemental lighting. Plants were transferred from the greenhouse to a controlled environment chamber at the end of civil twilight at a set developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Photosynthetically active radiation (400-700 nm) was measured with a quantum sensor (LiCor, Lincoln, NE) and was determined to be 900 µmol m -2 s -1 incident on the acrylic enclosure and between 600 and 800 µmol m -2 s -1 inside the enclosure at plant canopy height depending on internal shade and plant stature. For comparison, instantaneous light levels in the enclosure were about one-third of midlatitude peak values at the summer solstice, while daily integrals were about 25% greater than maximum average values outdoors (33). The 24 h photoperiod accelerated plant growth and avoided the need to recover respired 13 CO2 that would otherwise have been lost during nightly dark periods.…”
Section: Methodsmentioning
confidence: 99%
“…Photosynthetically active radiation (400-700 nm) was measured with a quantum sensor (LiCor, Lincoln, NE) and was determined to be 900 µmol m -2 s -1 incident on the acrylic enclosure and between 600 and 800 µmol m -2 s -1 inside the enclosure at plant canopy height depending on internal shade and plant stature. For comparison, instantaneous light levels in the enclosure were about one-third of midlatitude peak values at the summer solstice, while daily integrals were about 25% greater than maximum average values outdoors (33). The 24 h photoperiod accelerated plant growth and avoided the need to recover respired 13 CO2 that would otherwise have been lost during nightly dark periods.…”
Section: Methodsmentioning
confidence: 99%
“…Plants were illuminated by six 400-W high pressure sodium (Sylvania LU400/ECO, Osram Sylvania, Inc., Danvers, MA) and six metal halide lamps (Sylvania MS400/HOR, Osram Sylvania, Inc., Danvers, MA) configured in three separately controlled banks with two lamps of each type. The banks were programmed to turn on and off at intervals producing stepwise increases and decreases in light that simulated a diurnal cycle of irradiance, as well as, seasonal changes in lighting (22). Solstice conditions were 15 h daylength, 44.6 mol -2 daily integral of photosynthetically active radiation (PAR, quanta between 400 and 700 nm), and 825 µmol -2 s -1 average irradiance of PAR.…”
Section: Chemicalsmentioning
confidence: 99%
“…Wardlaw & Marshall () reported that allocation to starch increases in high light in Lolium and Sorghum . Comparing soybean across a set of natural light regimes at different times of the year, Britz () concluded that allocation to starch under natural light regimes was inversely related to photoperiod duration and to peak irradiance. However, as these two factors often co‐vary, it was unclear what contribution was made by irradiance.…”
Section: Introductionmentioning
confidence: 99%